Sociocultural factors associated with fish consumption in Lake Albert fishing community: Guidelines for lead and mercury - Tamale, Andrew; Ejobi, Francis; Muyanja, Charles; Naigaga, Irene; Nakavuma, Jessica; Kato, Charles D.; Amulen, Deborah R. (Cogent Environmental Science, 2017)
Fish consumption in subsistence fishing community is a life style associated with lead and mercury uptake for humans. Fish consumption is influenced by sociocultural factors, exposure and health risks. Unfortunately, no sociocultural study in the Lake Albert fishing community in light of lead and mercury exists. A crosssectional sociocultural study was carried out between March and June 2015. A total of 270 household heads in four landing sites in Hoima district completed structured questionnaires and data analyzed using SPSS version 20. The majority of the households (74.8%) had primary education or below, 51.1% drank unboiled water, and 30% perceived lake water safe for drinking. Children under five ate soup (15%) and middle piece of the fish (29%). The Poisson general linear model predicting weekly fish consumption amounts against sociocultural factors showed that household size (p = 0.047), male child presence (p = 0.007), methods of preparation i.e. salting (p < 0.0001), fish parts consumed by adults (p < 0.0001), fish preference (p < 0.0001), awareness about the beach management unit (p < 0.0001), and income from charcoal selling (p < 0.0001) were positive predictors. The negative predictors of weekly fish consumption amounts were awareness about fish consumption benefits (p < 0.0001), eating young fish (p = 0.002), donor agency presence (p < 0.0001), and frying as the method of fish preparation (p = 0.002). In conclusion, knowledge of
Keywords: heavy metal; lead; mercury; fish consumption advisory